2010
DOI: 10.1097/pep.0b013e3181dbeff0
|View full text |Cite
|
Sign up to set email alerts
|

The Clinimetric Properties of Performance-Based Gross Motor Tests Used for Children With Developmental Coordination Disorder: A Systematic Review

Abstract: The 2 highest scoring measures are recommended in the first instance for clinicians wishing to evaluate gross motor performance in children with developmental coordination disorder. However, both measures require further testing to increase confidence in their validity for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 42 publications
1
43
0
3
Order By: Relevance
“…Evidence is provided for the content and construct validity, and testretest and interrater reliability of the test for 4 years olds is provided. Slater et al (2010) ranked this test as 3rd out of 7. Deitz et al (2007) found that some test items are still quite difficult for typically developing 4 year olds and for 5 year olds with developmental delay.…”
Section: General Motor Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence is provided for the content and construct validity, and testretest and interrater reliability of the test for 4 years olds is provided. Slater et al (2010) ranked this test as 3rd out of 7. Deitz et al (2007) found that some test items are still quite difficult for typically developing 4 year olds and for 5 year olds with developmental delay.…”
Section: General Motor Assessmentmentioning
confidence: 99%
“…Its validity as a measure of motor impairment with young children (4-6 years) has been questioned (Brantner et al 2009) although Tan and colleagues (2001) found it to be a more accurate identifier of children (5-11 years) with motor impairment compared to the BOTMP. Slater et al (2010) considered some of the test items as unusual and the scoring system as difficult to interpret. The authors ranked this test as equal lowest with the Zurich Neuromotor Assessment which is primarily used in Switzerland (Blank et al 2012).…”
Section: General Motor Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some test items in the BOT-2 are still rather challenging for typically developing four year olds and for five year olds with developmental delay (Deitz et al, 2007). Additionally, the BOT-2 is time-consuming to perform and the score conversion is complicated (Slater et al, 2010).…”
Section: Measures Of Motor Co-ordinationmentioning
confidence: 99%
“…The MABC was ranked the highest in a systematic review evaluating the clinimetric properties of performance-based gross motor tests for children with DCD (Slater et al, 2010). Studies of the Test of Motor Impairment (Stott et al, 1984), the predecessor of the MABC, indicate that it was reliable and useful in identifying children with motor problems (Crawford et al, 2001).…”
Section: Measures Of Motor Co-ordinationmentioning
confidence: 99%